Forecasting Analysis of Heavy Equipment Repair Services Using the Time Series Method at PT Putra Jawamas - Azka Nurissyaban Achmad; Moch. Tutuk Safirin (Universitas KH. Abdul Chalim Mojokerto, 2025)
Forecasting is the art and science of predicting future events. Forecasting is an important thing to do research in companies, especially at PT Putra Jawamas, to provide ease in estimating resources and service needs. In companies engaged in the field of repair and fabrication, there are resource needs and service needs that must be prepared to maintain the stability and quality of services. Forecasting is a theory for estimating future events by involving the historical past retrieval. This company uses forecasting to estimate the demand for heavy equipment repair services in the future using the time series method, which is part of several methods, including single exponential smoothing, weighted moving average, and moving average. The research methods used are interviews, observations, historical data collection and literature studies related to this discussion. The results of this study indicate that the best research method of the weighted moving average and exponential smoothing methods for the demand for heavy equipment repair services at PT Putra Jawamas is exponential smoothing with α = 0.2 and the forecast for October 2023 is 4 units.